LOTS dan HOTS tentang tanaman obat: Pembelajaran sains dan lingkungan saat new normal COVID-19 - Ilmi Zajuli Ichsan; Diana Vivanti Sigit; Rizhal Hendi Ristanto; Ilena Amalia Luthfi; Dewi Robiatun Muharomah; Muhammad Efendi; Ruqiah Ganda Putri Panjaitan; Giry Marhento; Yeni Widiyawati; Susilo (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
Medicinal plants were contextual to study during Coronavirus Disease 2019 (COVID-19). The purpose of this study was to measure Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS) of medicinal plants and analyze the relevance of science learning during new normal COVID-19. The research method used descriptive quantitative with survey techniques carried out in 2019 and 2020. The instrument used12 items test question with a sample 104 vocational students. The results showed that the students' LOTS scores were higher (2.32) than students’ HOTS (1.69).Analysis showed that the topic of medicinal plants and the relevant environment during the new normal period of COVID-19. The conclusion from this study that the LOTS score was higher than HOTS and knowledge of medicinal plants became relevant during the new normal COVID-19.